Manufacturable Low Keff (Keff<2.5) Cu Interconnects by Selective / Low Damage Air Gap Formation - Harada, T.; Takahashi, M.; Murakami, K.; Korogi, H.; Sasaki, T.; Hattori, T.; Ogawa, S.; Ueda, T. (Proceedings of the IEEE International Interconnect Technology Conference, 2006)
A new technology for manufacturing low Keff (<2.5) Cu interconnects with air gaps has been first proposed and demonstrated. Key points in this technology are suppression of damage to lines during air gap formation and exclusion of air gaps by a carefully designed manner. Using this technology, Keff lower than 2.5 was realized without any degradation of yield, performance and reliability